Exploring geometric morphology in shape memory textiles: design of dynamic light filters - Cabral, Isabel (2015)
Thermo-responsive Shape Memory Alloys are able to adopt a temporary configuration and return to their programmed shape when heated to a determined activation temperature. The possibility to integrate them in textile substrates creates potential to develop smart textiles whose shape change explores functional and expressive purposes. The aim of this research is to develop shape memory woven textiles in which dynamic behavior achieves predefined geometric shapes. The requirement of geometric morphology was addressed through origami techniques. Combining foldability properties with shape change, it is possible to design textile structures with a variable number of layers. Difference in light transmittance is analyzed according to layer variation. Experiments conducted explore methodological processes aimed at future developments in dynamic light filters research. The results highlight a process to design textiles with predefined geometric morphologies that can be activated electrically, and delineate a further study in order to improve the shape memory textile behavior.